2021
DOI: 10.5860/crln.82.3.106
|View full text |Cite
|
Sign up to set email alerts
|

Surging virtual reference services: COVID-19 a game changer

Abstract: In March 2020, academic libraries across the United States closed and sent everyone home, some destined to not reopen for months. University offices closed. Classes were moved online. Suddenly, librarians and staff pivoted to working from home and to all remote services, without time for planning logistics or training. To study the impact of this extraordinary and sweeping transition on virtual reference services (VRS), we conducted a major study of academic library responses to the pandemic that focused on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…Beyond recounting events and addressing the immediate and practical considerations of the closures, the first major theme identifiable in the literature was the lack of access to print reserves or textbooks in the move to fully online learning (Archer-Helke et al , 2021; Dar, 2020a; Radford et al , 2021; Rafiq et al , 2021). Libraries may purchase hard copies of textbooks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond recounting events and addressing the immediate and practical considerations of the closures, the first major theme identifiable in the literature was the lack of access to print reserves or textbooks in the move to fully online learning (Archer-Helke et al , 2021; Dar, 2020a; Radford et al , 2021; Rafiq et al , 2021). Libraries may purchase hard copies of textbooks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreshadowing the longer-term and more substantial studies to come, in March 2021, an item in College and Research Libraries News (Radford et al , 2021) previewed the results of a longitudinal 300-respondent survey of academic libraries. This highlighted how readers can expect different stages to the published research on libraries during the pandemic, covering short- and long-term impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Preliminary results of research that includes a national survey and in-depth interviews with managers/directors of live chat services in academic libraries reveals an increase in virtual services, driven by the COVID-19 related closure of nearly all physical library buildings for an extended period of time beginning in March 2020. 5 Anecdotal evidence, including VRS how-to's and case studies, have also emerged in practitioner literature and services such as Springshare have experienced a 267% increase in total chats when comparing February to August 2020 across the US, Canada, Europe, and Australia. 6 People's use of social media as an information source has also grown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the strongest areas of growth for virtual reference services during the pandemic has been chat reference. In a longitudinal survey of 300 academic librarians during the pandemic in the US, Radford, Costello, and Montague (2021) found that 71% of respondents reported an initial increase in demand for their virtual chat reference at the outset of the pandemic. They also report that many libraries expanded their chat reference services (Radford, Costello & Montague, 2021), and in another conference presentation, report an increase in question complexity (Radford, Budd, Connaway, & Costello, 2021).…”
Section: Chat Reference Expansion and Innovationsmentioning
confidence: 99%
“…Many other libraries expanded hours for their chat reference services (Radford, Costello & Montague, 2021;Dar, 2020;Dodd & Kotaska, 2020, Kooyman, 2021. This allowed libraries to accommodate increasing numbers of chat questions, and to help students who may not be in the same time zone as the library.…”
Section: Chat Reference Expansion and Innovationsmentioning
confidence: 99%